PERANCANGAN WEBSTE PROMOSI KEPARIWISATAAN KOTA PADANGSIDIMPUAN - NOVITA SARI SITUMORANG, Drs. Syafwan, M.Si., Drs. Ir. Heldi, M.Si., Ph.D. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Tourism information in Padangsidimpuan about history, geographic location, nature turism, city icons, and culinarys is lacking. The potential palace is the main factor of the author to design a promotion website for tourism in Padangsisimuan city. The website is the medium thats widely used in todays modern era. This due to rapid technological decvelompment and needs communicaty to get information quickly and accurate with a wide audiences. The method of designing website promotion of Padangsidimpuan city start from collecting data through observations, interviews, and documentations. So thats problem can be known and identification of the problem can be analyzed using the 5W+1H theory (What, Who, Where, When, Why, How). The method can helping to solve problems and trigger the emergence of ideas to solve problems in the design website to promotion tourism in Padangsidimpuan city. The main medium used in this promotion is website with supporting media such as poster, web bnner, key chains, t-shirts, stickers, mug, and pocket books.Keyword : Website, Promotion, Tourism